Relation between Significance of Attribute Set and Single Attribute - Ma, Xiuqin; Norrozila, Sulaiman; Qin, Hongwu (International Scholarly and Scientific Research & Innovation, 2010)
In the research field of Rough Set, few papers concern the significance of attribute set. However, there is important relation between the significance of single attribute and that of attribute set, which should not be ignored. In this paper, we draw conclusions by case analysis that (1) the attribute set including single attributes with high significance is certainly significant, while, (2)the attribute set which consists of single attributes with low significance possibly has high significance. We validate the conclusions on discernibility matrix and the results demonstrate the contribution of our conclusions.